Hubungan Kasus Demam Berdarah Dengue dengan Kepadatan Penduduk di Jawa TimurTahun 2019-2020 - Nely Sintia; Lucia Yovita Hendrati (Media Gizi Kesmas, 2023)
Background: Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus. Indonesia has been an endemic country for dengue hemorrhagic fever since 1968. There are several factors related to the occurrence of dengue hemorrhagic fever, one of which is the human factor and that is population density. Objective: The aim of this study is to analyze the relationship between dengue hemorrhagic fever cases and population density in East Java Province in 2019-2020. Method: This study uses a cross-sectional design. The data used in this study are secondary data collected in 2019-2020from the province of East Java Health Profile. Data analysis used the Shapiro-Wilk test to determine the normality of the data and then the Spearman correlation test to determine the relationship between variables. Result: The result of Spearman correlation test between cases of dengue hemorrhagic fever (DHF) and the population density showed a correlation with P = 0.033 in 2019 and p = 0.007 in 2020 where p <0.05. The strength of the relationship shows a moderate relationship with a negative relationship direction, the correlation coefficient value = -0.348 in 2019 and the correlation coefficient = -0.429. If the population density increases, the case of dengue hemorrhagic fever will decrease. Conclusion: As a result of the research, there is a relationship between cases of dengue hemorrhagic fever and population density in East Java province in 2019-2020.